2016
DOI: 10.1002/2016gl069049
|View full text |Cite
|
Sign up to set email alerts
|

A scalable model for methane consumption in arctic mineral soils

Abstract: Recent field studies have documented a surprisingly strong and consistent methane sink in arctic mineral soils, thought to be due to high‐affinity methanotrophy. However, the distinctive physiology of these methanotrophs is poorly represented in mechanistic methane models. We developed a new model, constrained by microcosm experiments, to simulate the activity of high‐affinity methanotrophs. The model was tested against soil core‐thawing experiments and field‐based measurements of methane fluxes and was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Priemé and Christensen, 1997) and emphasized in local mechanistic models (e.g. Oh et al, 2016). These finding suggest that the soil CH 4 sink in such ecosystems may be more sensitive to future change as a result of global warming.…”
Section: Seasonal Variabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…Priemé and Christensen, 1997) and emphasized in local mechanistic models (e.g. Oh et al, 2016). These finding suggest that the soil CH 4 sink in such ecosystems may be more sensitive to future change as a result of global warming.…”
Section: Seasonal Variabilitymentioning
confidence: 78%
“…Sabrekov et al (2016) developed a process-based model of soil CH 4 uptake that also incorporates rhizosphere methanotrophy. Oh et al (2016) developed a model (XHAM) that explicitly simulates high-affinity methanotrophy and active microbial biomass dynamics. These models are driven by highresolution local data sets, which presents challenges for conducting global simulations of soil methanotrophy because of limited availability of input data necessary to drive the models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, researchers tracked 13 C-labeled CH 4 into the DNA of bacteria that were closely related to known methanotrophs such as Methylomonas, Methylococcus, and Methylocystis/Methylosinus (Hutchens et al, 2004). In a recent study of the semiarid Wellington Caves in Australia, up to 16% of the 16S rRNA gene sequences recovered from cave soils belonged to groups of known methanotrophs (McDonough et al, 2016). The high relative abundance of methanotrophs in these systems suggests that microbially mediated CH 4 oxidation should be important in at least some caves.…”
Section: Strong Experimental Support For the Importance Of Biotic Cmentioning
confidence: 99%
“…Previous studies have found that Arctic tundra ecosystems have shifted from net CO 2 sinks to sources (Belshe et al, ; Oechel et al, ); whether they behave as sinks or sources of atmospheric CH 4 largely depends on local microtopography (Jørgensen et al, ; Nauta et al, ; Oh et al, ; Tan et al, ). Minor changes in surface elevation might shift Arctic soils from sinks to sources of atmospheric CH 4 (Olivas et al, ; Zona et al, ).…”
Section: Introductionmentioning
confidence: 99%